PENINGKATKAN PENGUASAAN MEMAHAMI OPERASI BILANGAN BULAT MELALUI TEHNIK PAIKEM THE POWER OF TWO SISWA SMP - ., Cahye . (Jurnal Pembelajaran Prospektif, 2019)
This research was aimed to find out the process of activities in an effort to improve mastery of understanding integer operations through the PAIKEM technique The Power Of Two (strength of two peoples) in class VII A Junior High School 3 Kubu. Mastery of understanding integer operations by students in mathematics learning is still low, so that the learning was unpleasant and uninteresting. Therefore, we need a learning technique that is able to improve mastery of understanding by students so that it can also improve learning outcomes. The method used is the method of discussion. Results of this study are indicated by an increase in mastery of understanding integer operating material by students in learning. In the first cycle of meeting 1 obtained 60.25%, and meeting 2 obtained 62.73%. In the second cycle meeting 1 obtained 79.87% and meeting 2 obtained 79.50% with the mastering category.